EFFECT OF INCLUSION OF CORN GERM MEAL IN DIETS OF COLORED (RAJA-II) BROILERS WITH PHYTASE ENZYME SUPPLEMENTATION - R. K. SOWJANYA LAKSHMI; R. G. GLORIDOSS; K. CHANDRAPAL SINGH; H. N. N. MURTHY (The Bioscan, 2015)
An experiment was conducted with an objective to study the growth performance of colored broiler chicken fed with corn germ meal (CGM) based diets and to access effect of supplementation of phytase enzyme in CGM based diets on production performance. Eight dietary treatments were prepared by partly replacing maize and soya bean meal (SBM) with 0, 15, 20 and 25% of CGM with put and without phytase enzyme (conc. 2500 IU/g) supplementation at 0.05 percent. Body weight gain, feed intake FCR and livability were estimated for every week and also cumulatively. Cumulative body weight gain of birds ranged from 1369 to 1202 gm differing significantly (p<0.05) between 0% CGM groups without and with phytase supplementation but not in other groups. Feed consumption, FCR and livability were not differing significantly (p>0.05). The production performance in terms of both performance index scores (PIS) and economic index score (EIS) were ranging from 129.4 (0% CGM with phytase) to162.5 (0% CGM without phytase) for PIS and 6.653 (25% CGM without phytase) to 8.687 (0% CGM without phytase) for EIS values. Results indicate that CGM can be included in the diets of colored broilers without or with phytase enzyme supplementation up to 25 percent level.